Optimizing the Role of Indonesian Broadcasting Commission in the Context of Disseminating Health Information during the Covid-19 Pandemic - Aju Putrijanti, Kadek Cahya Susila Wibawa, Megawati Purnamasari, Henny Juliani, (Pakistan Journal of Medical & Health Sciences, 2022)
Introduction: Information technology is developing very rapidly along with the emergence of the Covid-19 Pandemic. Various information related to Covid-19 delivered by broadcasters is required to be strictly monitored to ensure that the information received by the public is correct and valid. The Indonesian Broadcasting Commission has the authority to monitor the broadcasting. Objectives: This paper aimed to analyze the optimization of the role of the Indonesian Broadcasting Commission to monitor the spread of health information during the Covid-19 pandemic. Research Methodology: This study combined doctrinal law research and non-doctrinal legal research. The research specification was descriptive-analytical and the analysis was carried out qualitatively. Conclusion: The Indonesian Broadcasting Commission has not optimally carried out its duties and roles in monitoring the dissemination of information related to the Covid-19 pandemic. Institutional strengthening, institutional synchronization at the central and regional levels, and increasing the capacity of Commissioners are some efforts to optimize the roles and tasks of the Indonesian Broadcasting Commission in the future. Keywords: Indonesian Broadcasting Commission; Health Information; Covid-19 Pandemic.